2021
DOI: 10.1111/fcre.12590
|View full text |Cite
|
Sign up to set email alerts
|

The View from the Other Side: How Parents and their Representatives View Family Court

Abstract: This qualitative study brings together the voices of parents and their representatives, including attorneys, social workers and parent advocates, to understand the lived experiences of child welfare involved parents as they navigate Family Court, and how to improve it. The findings suggest that these courts are difficult to navigate for both parents and their representatives, and are often experienced as punitive and unsupportive spaces. The findings also reveal a strong congruence between how parents and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 23 publications
(51 reference statements)
0
31
0
Order By: Relevance
“…Second, the majority of attorneys touched on a challenge often encountered in the courtroom: the wish to provide their client with an opportunity to advocate directly to the judge while remaining in control of the client's “image”. These attorneys may be acutely aware of the ways in which their overwhelmingly Black clients are negatively perceived in largely White courtrooms (Lens, 2019; Stephens et al, 2021). Numerous participants reported that many of the parents they had served felt strongly about communicating directly to the judge in their efforts to regain custody of their children, but that sometimes these opportunities back‐fired, instead showcasing a version of the parent as volatile or angry.…”
Section: Discussion and Practice Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the majority of attorneys touched on a challenge often encountered in the courtroom: the wish to provide their client with an opportunity to advocate directly to the judge while remaining in control of the client's “image”. These attorneys may be acutely aware of the ways in which their overwhelmingly Black clients are negatively perceived in largely White courtrooms (Lens, 2019; Stephens et al, 2021). Numerous participants reported that many of the parents they had served felt strongly about communicating directly to the judge in their efforts to regain custody of their children, but that sometimes these opportunities back‐fired, instead showcasing a version of the parent as volatile or angry.…”
Section: Discussion and Practice Implicationsmentioning
confidence: 99%
“…However, they can enhance the collaboration between the parent and their legal team, and, more importantly, they can provide parents with the critically important opportunity to have their voices heard directly by those who will be making decisions about their families. While these court hearings may feel commonplace and somewhat routine for those on the legal team, the stakes could not be higher for parents seeking to regain custody of their children (Stephens et al, 2021). The ability to express themselves in court may help these parents in the process of regaining custody even when they have not been formally prepped by their legal teams; past studies in Drug Treatment Courts have shown that participants who feel as though they were provided with judicial praise and support in the courtroom tend to be more motivated to change and to more readily accept judicial mandates and decisions (Rossman & Zweig, 2011; Satel, 1998; Senjo & Leip, 2001).…”
Section: Discussion and Practice Implicationsmentioning
confidence: 99%
“…These include “being thoughtful about what information they share about parents in court and why”; creating collaborative courtrooms where parents are empowered by asking what they think needs to happen for their children to safely return home; helping parents be prepared for what will happen in court; avoiding a punishing attitude toward parents and celebrating accomplishments; and offering parents trauma‐informed services (Stephens et al, p. 15). Bench books and bench cards help educate judges about structural, explicit, and implicit bias, provide a tool to help recognize and prevent bias, and offer concrete strategies to counter their own tendencies toward stereotyping and bias (Stephens et al, 2021, p. 15).…”
Section: Part Iii: Recommendations: Using Judicial Discretion To Comb...mentioning
confidence: 99%
“…The whole floor is people that are like me…You ’ re like, this is not gonna go well . (Stephens et al, 2021, p. 10).…”
mentioning
confidence: 97%
“…The nuance provided by Elena's lived experiences, and other PAs like her, resonates with parents who have faced similar hurdles in lives. These parents often do not feel understood by the workers and service providers who engage with them, and this can be incredibly isolating (Stephens et al, 2021). Having a space where they feel seen and understood, without needing to explain or defend themselves, is rare and necessary.…”
Section: Post‐scriptmentioning
confidence: 99%